RESEARCH WORK AT OHIO STATE UNIVERSITY. - Bell, Spurgeon (The Accounting Review, 1926)
Abstract The research program of any college of commerce ought to give first consideration to the educational situation but the second function is also a matter of importance particularly when it will always be necessary in undertaking any business research to get the cooperation of businessmen who can furnish with proper facilities. There are certain studies that are growing out of those that were previously made. One of these is a study of the unit selling expense and involves a comparison between those establishments which employ salesman on a commission basis, those where salesman are employed on a salary basis and those concerns which employ salesman on a mixed basis. The independent accountants who are the accountants, one might say, of Ohio and particularly those who do not represent the large accounting firms with many branches are interested in a project that will involve a study of expense ratios and balance sheet ratio with which one is familiar. Whether the accounting firms will cooperate by furnishing with information in regard to revenue statements and assets has not been fully determined. Two studies are being conducted at Ohio State which have not been classified as accounting studies and yet which seem to be likely to degenerate into accounting studies. One of these is the study of merchandise control.